Impak pembangunan Langkawi ke atas corak pekerjaan dan guna tenaga di Pulau Dayang Bunting, Langkawi - Ishak Yussof,; Mustaffa Omar,; Gusni Saat, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2007)
This article analyses occupation and employment pattern amongst community in Pulau Dayang Bunting, Langkawi. Data for this study is gathered via questionnaire administered using census method through a fieldwork conducted in May-June 2005. We used frequency distributions and cross tabulation method to analyse data related to the community’s economics activities. The analysis is important to evaluate the impact of Langkawi development on the labour participation rate and unemployment problems, employment structure and types of occupation, and the implication on their income level. The analysis focuses on the characteristics and types of occupation (main and part-time jobs), employment structure by sector, income, skills and their level of education. Issues and problems related with the current occupation and employment status of the respondents are also discussed. Our study shows that the labour force is shrinking due to the outflow of the productive labor force to the main island of Langkawi. They prefer to commute or moved to the main island since most occupations are located in Kuah or the surroundings. Our observation during the fieldwork shows that modern economic activities are very limited and is not expanding in Pulau Dayang Bunting. In contrast, the community economic activities concentrated mainly on traditional economic activities, in particular fishing and agriculture. Unemployment rate in Pulau Dayang Bunting is relatively high due to limited job opportunity compared with other area in the mainland of Langkawi